2009
DOI: 10.1111/j.1532-849x.2008.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant‐Retained Nasal Prosthesis for a Patient Following Partial Rhinectomy: A Clinical Report

Abstract: Prosthetic rehabilitation of facial defects has always perplexed maxillofacial prosthodontists. Facial defects lead to functional and cosmetic deficiencies. Early rehabilitation improves patients' quality of life. Osseointegrated rehabilitation of the maxillofacial prosthetic patient presents the potential for overcoming many of the disadvantages associated with conventional retentive methods. This paper presents the clinical report of a patient who had undergone partial rhinectomy due to basal cell carcinoma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Alpha sites are 6 mm or greater in axial bone volume. The most common areas of the facial skeleton having this volume of bone are the anterior maxilla through the nasal fossa (floor of the nose) and the zygoma [15]. …”
Section: Case Presentationmentioning
confidence: 99%
“…Alpha sites are 6 mm or greater in axial bone volume. The most common areas of the facial skeleton having this volume of bone are the anterior maxilla through the nasal fossa (floor of the nose) and the zygoma [15]. …”
Section: Case Presentationmentioning
confidence: 99%
“…Ciocca et al described a prosthetic rehabilitation using an implantretained silicone nose for a patient after a total rhinectomy [7]. Rodrigues et al and Guttal et al respectively described a nose prosthetic treatment using acrylic resin for a patient after a partial rhinectomy [8,9]. Seçilmiş et al reported a treatment using a silicone nasal prosthesis with an undercut-retained design for a patient after a partial rhinectomy [10].…”
Section: Introductionmentioning
confidence: 99%
“…The face being the most noticeable part of the body when disfigured may lead to an impaired social life stemming from esthetic problems [1,2]. Among facial defects, nasal defects produce severe cosmetic impairment.…”
Section: Introductionmentioning
confidence: 99%